Fast and efficient approach for multi-component quantum wells analysis based on FFT. (December 2021) - Pawlaczyk, L.; Pucicki, D.; Serafinczuk, J.
Highlights: The presented method allows analysis of the periodic structures in aspect of their thickness. The method is sensitive to thickness changes of up to 1 nm. The use of the FFT algorithm allows to shorten the total time of sample analysis. Abstract: Elaboration of the technology of the multicomponent Quantum Wells (QWs) based devices requires repeated time consuming diffraction curves analysis proceeded for each of the grown structures to determine their basis structural parameters. Optimization of the diagnostic procedures and making them more efficient is the key point from the manufacturer point of view. In this paper we present the use of Fast Fourier Transform (FFT) employed to fast determination of the thickness of epitaxial layers. The presented method combines the approach using the Rocking Curves (RC) measured by X-ray Diffraction (XRD) together with the analysis of the FFT spectrum. In this work GaInNAs/GaAs MQWs structures grown by atmospheric pressure-metalorganic vapour phase epitaxy (AP-MOVPE) were investigated. In the case of the series of the defined type samples, this method allows replacement of the time consuming simulation method used for diagnostic of the thickness of deposited layers in favor of FFT spectrum analysis.